Rift Valley Fever Virus Seroprevalence among Humans, Northern KwaZulu-Natal Province, South Africa, 2018–2019 - Pawęska, Janusz T.; Msimang, Veerle; Kgaladi, Joe; Hellferscee, Orienka; Weyer, Jacqueline; Jansen van Vuren, Petrus (Emerging infectious diseases, 2021)
We detected Rift Valley fever virus (RVFV) IgM and IgG in human serum samples collected during 2018-2019 in northern KwaZulu-Natal Province, South Africa. Our results show recent RVFV circulation and likely RVFV endemicity in this tropical coastal plain region of South Africa in the absence of apparent clinical disease.